Remaking Eden : cloning and beyond in a brave new world (Weiden and Nicolson, 1998)
The author, a leading molecular biologist, discusses the moral, ethical and legal implications of human cloning and genetic engineering. Includes information on current and future changes in giving birth, from IVF and surrogacy to male pregnancy and genetic design of children.